2023
DOI: 10.1371/journal.pone.0286299
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-biometric characterization of indigenous chicken ecotypes in north-western Ethiopia

Abstract: Morphological characterization of Animal Genetic Resources is the first step to documenting diversity and designing breed specific breeding programs. The current study characterized the morpho-biometric variation of indigenous chicken ecotypes prevailing in northwestern Ethiopia. A multi-stage purposive, stratified, and random sampling method was employed to select the study areas and chickens. A total of 1200 adult chickens were sampled and characterized for 12 qualitative and 11 quantitative traits. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[ 64 ], who suggested that achieving a 100% accurate classification of animals to their original population based on phenotypic measurements is challenging.Muluneh et al . [ 25 ] also reported contrasting results, indicating that the overall classification rates for the female and male chicken populations were 57.47% and 69.97%, respectively, in the three zones of the Amhara National Regional State of Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 64 ], who suggested that achieving a 100% accurate classification of animals to their original population based on phenotypic measurements is challenging.Muluneh et al . [ 25 ] also reported contrasting results, indicating that the overall classification rates for the female and male chicken populations were 57.47% and 69.97%, respectively, in the three zones of the Amhara National Regional State of Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distance between male ecotypes was greater than that reported in previous research on Muscovy ducks [ 31 ]. Additionally, small distances were reported between chicken ecotypes in Saudi Arabia [ 57 ],the central zone of Tigray [ 20 ], and three zones of the Amhara National regional state of Ethiopia [ 25 ]. These findings contrast with the research on indigenous, commercial layer, and broiler chickens in Jordan [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations